Komunikasi Terapeutik dalam Tinjauan Konseling Analisis Transaksional Perawat-Pasien - Rahmawati Rahmawati; Nurus Sa’adah (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2022)
The nurse-patient relationship in the communication process aims to solve the problems faced by nurses and patients is called therapeutic communication. This article discusses therapeutic communication in a review of nurse-patient transactional analysis counseling. Therapeutic communication is very important in nursing, nurse-patient communication aims to serve patients. Good therapeutic communication will build a trusting nurse-patient relationship. This study aims as a reference material for hospitals in order to implement good nurse-patient communication. This study uses the literature review method, the author only reads existing journals and then develops it into a writing. The result of this study is that therapeutic communication produces a lot of I'am Ok-You Are Ok life positions, but it is possible that a small number of nurses do not use therapeutic techniques properly. The novelty of this paper is related to therapeutic communication in nurse-patient transactional analysis counseling using a good life position when nurses provide informing techniques, open questions, focus, listen attentively, identify themes and suggestions. The limitation of this research is that it only focuses on the life position in transactional analysis counseling.